2018
DOI: 10.1111/tbed.13050
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors analysis of bovine tuberculosis in cattle raised in mixed crop‐livestock farming system in Tigray region, Ethiopia

Abstract: Prevalence and risk factors analysis of bovine tuberculosis in cattle raised in mixed crop-livestock farming system in Tigray region, Ethiopia', Transboundary and Emerging Diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…Many risk factors were responsible for occurrence of disease in animals include cattle breed, age. also host independent factors are considered more important and include herd size, management practices and cattle purchasing (5)(6)(7)(8)(9). Diagnosis of BTB in live animal depends on tuberculin test; the standard method is the comparative intradermal tuberculin (CIDT) test which based on delayed hypersensitivity (10).…”
Section: Introductionmentioning
confidence: 99%
“…Many risk factors were responsible for occurrence of disease in animals include cattle breed, age. also host independent factors are considered more important and include herd size, management practices and cattle purchasing (5)(6)(7)(8)(9). Diagnosis of BTB in live animal depends on tuberculin test; the standard method is the comparative intradermal tuberculin (CIDT) test which based on delayed hypersensitivity (10).…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study of bTB in Ethiopia, exotic cattle were more likely to be bTB positive using the comparative cervical intradermal tuberculin test (CIDT) than local cattle breeds (Habitu et al, 2019). A meta-analysis of bTB in Ethiopia also found that Holstein-Friesians have a higher bTB prevalence than local zebu [prevalence = 21.6% (95% CI: 14.7-30.7); prevalence = 4.1% (95% CI: 3.4-4.9), respectively (Sibhat et al, 2017)].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ameni et al (2007) found that Holsteins had more severe bTB pathology than zebu cattle in Ethiopia. Therefore, the use of and/or crossbreeding with taurine dairy cattle and the intensification of farming is likely to increase the incidence of bTB (Habitu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study of bTB in Ethiopia, exotic cattle were more likely to be bTB positive using the comparative cervical intradermal tuberculin test (CIDT) than local cattle breeds (Habitu et al, 2019). A meta-analysis of bTB in Ethiopia also found that Holstein-Frisians have a higher bTB prevalence than local zebu (prevalence = 21.6% (95% CI: 14.7–30.7); prevalence = 4.1% (95% CI: 3.4–4.9), respectively) (Sibhat et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…(Ameni et al, 2007) found that Holsteins had more severe bTB pathology than zebu cattle in Ethiopia. Therefore the use of and/or crossbreeding with taurine dairy cattle and the intensification of farming is likely to increase the incidence of bTB (Habitu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%